VD_FINDINFO Décision / 2014 / 1127 vom 10. Oktober 2014 - VD Tribunal cantonal (2014)
AVANCE DE FRAIS, AUTOPSIE, CADAVRE, OBLIGATION DE PRODUIRE DES PIÈCES | 253 al. 3 CPP (CH), 265 al. 3 CPP (CH), 265 CPP (CH), 313 al. 2 CPP (CH), 313 CPP (CH)